Depression and Anxiety as Aspects of Mental Health in Celiac Disease: A Systematic Review and Meta-Analytical Synthesis - Martowska, Julia; Wojciechowska, Karolina; Warych, Wiktor; Parol, Maciej; Klemendorf, Nicole Monika; Baran, Julia; Niezgoda, Julia; Skłodowski, Tomasz; Woroniecka, Katarzyna; Bullmann, Agnieszka (Quality in Sport, 2026)
Background: Celiac disease (CD) is a chronic immune-mediated disorder with significant extraintestinal manifestations, including neuropsychiatric symptoms. Depression and anxiety are among the most frequently reported and may substantially affect quality of life. Aim: This review aimed to evaluate the prevalence of depressive and anxiety symptoms in adults and children with CD and to assess the influence of adherence to a GFD on psychiatric outcomes. Material and Methods: A structured narrative review with meta-analytical synthesis was conducted using studies identified through PubMed/MEDLINE, Scopus, and Web of Science. Observational studies, clinical cohorts, and existing meta-analyses were included. Findings were integrated narratively, considering age, disease status, and dietary adherence. Results: Depressive symptoms were consistently more prevalent in individuals with CD, particularly in untreated or newly diagnosed patients. Partial improvement was observed following initiation of a gluten-free diet although symptoms often persisted. Findings regarding anxiety were heterogeneous. Psychiatric outcomes were influenced by disease activity, age, nutritional status, and psychosocial factors. Conclusions: Depression and anxiety are clinically relevant but often underrecognized components of CD. A GFD may alleviate psychological distress but does not fully eliminate psychiatric morbidity, supporting the need for routine mental health screening and multidisciplinary care.